In Vitro Differentiation of Human Neural Progenitor Cells Into Striatal GABAergic Neurons. (13th May 2015) - Lin, Lin; Yuan, Juan; Sander, Bjoern; Golas, Monika M.
Abstract: : Huntington's disease (HD) results from a CAG repeat expansion in the gene encoding the huntingtin protein. This inherited disorder is characterized by progressive neurodegeneration. In particular, HD progression involves the loss of striatal projection neurons. The limited availability of reliable sources of human striatal projection neurons currently hampers our understanding of HD mechanisms and hinders the development of novel HD treatments. In this paper, we described two- and three-step methods for differentiating human neural progenitor cells toward striatal projection neurons. In the two-step differentiation protocol, 90%, 54%, and 6% of MAP2-positive cells were immunopositive for GABA, calbindin (CALB1), and DARPP-32/PPP1R1B, respectively. In the three-step differentiation protocol, 96%, 84%, and 21% of MAP2-positive cells were immunopositive for GABA, calbindin, and DARPP-32/PPP1R1B, respectively. In line with a striatal projection neuron phenotype, cells differentiated with our protocols displayed significantly increased expression of MAP2, CALB1, DARPP-32/PPP1R1B, ARPP21, and CTIP2 . Application of glutamate receptor agonists induced calcium influx; accordingly, the cells also expressed various ionotropic glutamate receptor subunits. Differentiated cells also released GABA on stimulation. We suggest that our three-step differentiation protocol presents a reliable and simplified method for the generation of striatal projection neurons, yielding a critical resource for neuronal physiology and neurodegenerative disorder studies. Significance: The earliest changes in the neurodegenerative disorder Huntington's disease affect a specific type of brain neurons, the so-called medium spiny neurons of the striatum. In this study, two protocols were developed for the differentiation of neural progenitor cells into striatal medium spiny neurons, and the differentiated neurons were extensively characterized. The data indicate that the three-step differentiation protocol presents a reliable and simplified method for the generation of striatal medium spiny neurons. The generated striatal medium spiny neurons could represent a critical resource for the study of neurodegenerative disorders, a model system for drug discovery, and a step toward cell-based regeneration therapies. Abstract : The limited availability of reliable sources of human striatal projection neurons currently hampers understanding of Huntington's disease mechanisms and hinders the development of novel treatments. In this study, two protocols were developed for the differentiation of neural progenitor cells into striatal medium spiny neurons, and the differentiated neurons were extensively characterized. The data indicate that the three-step differentiation protocol presents a reliable and simplified method for the generation of striatal medium spiny neurons.